Pengaruh Leverage, Ukuran Perusahaan dan Capital Intensity Terhadap Agresivitas Pajak - Devia Herliyana; I Ketut Wenten (Masyarakat Ekonomi Syariah Bogor, 2025)
The aim of this research is to empirically test the influence of leverage, company size and capital intensity on tax aggressiveness. Leverage in this study is measured using the debt to asset ratio (DAR), company size is measured using the natural logarithm of total sales (LN TR), capital intensity is measured using the capital intensity ratio (CIR) and tax aggressiveness is measured using the effective tax rate (ETR). The population used in this research were property and real estate sector companies listed on the Indonesia Stock Exchange in 2018 - 2022. Using a purposive sampling technique, 15 companies were obtained as samples. This research uses secondary data in the form of audited financial reports and company annual reports obtained from the official IDX website, namely www.idx.co.id and also the official websites of each company. Hypothesis testing uses multiple linear regression analysis with the help of e-views version 12 software. The test results prove that: (1) leverage has an effect on tax aggressiveness, (2) company size has no effect on tax aggressiveness, (3) capital intensity has an effect on tax aggressiveness.